Solitary Fibrous Tumour of Cheek: A Diagnostic Dilemma - Yadav, Subhash; Kane, Shubhada (Annals of Pathology and Laboratory Medicine, 2020)
Solitary fibrous tumor (SFT), an uncommon spindle cell neoplasm is believed to be of mesenchymal origin and usually presents as pleural based mass. SFT are rare in the head-neck region but are extremely uncommon intra-orally. The patient was a young male who presented with difficulty in mouth opening. Examination revealed a submucosal nodule on the buccal surface which was histologically and immunohistochemically proven to be SFT. Authors wish to discuss the case due to its rarity and diagnostic difficulties due to many common histological mimickers at that site.